Approach to self-publishing with a combination of bibliometric study and social network analysis techniques. Issue 6 (7th November 2016) - Mangas-Vega, Almudena; Gómez-Díaz, Raquel; Cordón-García, José Antonio
Abstract : Purpose: From the point of view of the book chain, self-publishing is becoming increasingly common and it is doing so faster in the commercial world than in science. This study aims to analyse the phenomenon of self-publishing from the point of view of the research being done on it. Thus, in addition to studying the subject, it is going to be possible to analyse the viability of this methodology as an analysis technique. Design/methodology/approach: The methodology is based on a combination of traditional bibliometric studies and analysis of social networks applied. Findings: Self-publishing is a phenomenon that is being studied by the scientific community. But the research on this topic has a low rate of co-authorship and a low relationship between the most prolific authors and their relevance. The combination of techniques used has proven to be a very good choice for analyzing the data. Originality/value: There are not enough works analyzing the research in self-publishing. Because of the peculiarities of the topic, a combination of various techniques will provide a better approach to its study, so, this paper contains some results using bibliometrics and others using social network analysis applied.